Market Segmentation and the Association between Municipal Financial Disclosure and Net Interest Costs - Ehsan H. Feroz; Earl R. Wilson (The Accounting Review, 1992)
[This study provides evidence that market segmentation affects the strength of the association between financial disclosure and net interest cost for new issues of municipal bonds. Previous studies (see, e.g., Amershi and Ramamurtie 1990; Cook 1982; Hendershott and Kidwell 1978; Kidwell et al. 1983) show that the geographic segmentation of primary markets for municipal bonds along regional and national lines is characterized by different sources and costs of information. Because little information is available from alternative sources for the less marketable bonds of smaller issuers which use regional markets, financial reporting variables are hypothesized to be associated more strongly with interest costs for these issues than for those of larger municipalities, whose bonds are typically issued in the national bond market. Cook (1982) argues that the costs of obtaining information about small issuers from alternative sources are relatively high. For these issuers, who also do not issue bonds frequently, regional underwriters may be the only informational intermediaries (other than rating agencies if the bonds are rated) between the issuers and investors (Kidwell et al. 1983). Thus, financial and other entity-specific information contained in the offering statement are expected to be weighted more heavily in pricing these bonds than for bonds of larger issuers. Although this differential-information hypothesis is analogous to Atiase's (1985) argument regarding differential predisclosure of information, our study assumes differential availability of information across market segments, and size alone is not likely to be an adequate proxy for segmentation. Our main analysis uses the nature of the underwriting syndicate, whether it is managed by a national or regional underwriter, to proxy for the relevant market segment. Previous studies of municipal accounting (see, e.g., Ingram and Copeland 1982; Wallace 1981; Wilson and Howard 1984) have provided evidence of an association between bond measures and accounting and auditing variables. However, the results were mixed and inconsistent, which may be attributable to differences in the entities examined (cities, counties, and school districts), the time periods examined, or definitions of variables. Also, differences in the mix of bonds issued in each segment may have contributed to the inconsistent results. By examining the relationship between accounting and auditing variables and bond interest costs separately for each segment of the primary bond market, our study provides useful evidence on the potential effect of different information environments on this relationship. Regression results based on a sample of 119 new municipal bond issues, partitioned on a measure of segmentation (regional vs. national underwriter), are consistent with the hypothesis that the association between the quality and quantity of financial disclosure and interest costs is stronger for municipalities that issue bonds in local or regional markets than for those that issue bonds in the national market. Our results suggest that future research in this area should consider the potential effects of market segmentation when testing the association between accounting or auditing variables and bond interest costs.]